An Analysis of The Impact of Online Games on Social Development Among Students at SD IT Al - Husnayain: an Erikson Perspective - Fadlan Masykura Setiadi; Khairunnisa Khairunnisa (PGMI IAIN Lhokseumawe, 2026)
This study aimed to empirically examine the impact of online game usage on the social development of fourth-grade students at SD IT Al-Husnayain, Mandailing Natal, using Erikson’s psychosocial development theory as an analytical framework. The research employed a descriptive qualitative approach, with data collected through non-participant observation, semi-structured interviews with teachers and parents, and supporting documentation. The research subjects included fourth-grade students, classroom teachers, and parents selected through purposive sampling. Data were analyzed through thematic stages consisting of data reduction, data display, and conclusion drawing. The findings indicated that the majority of students engage in online gaming with high intensity, spending more than two hours per day on gaming activities. This condition has contributed to shifts in children’s social behavior, as reflected in increased verbal conflicts, the use of aggressive language, emotional outbursts, and a decline in the quality of social interactions within both school and family environments. From Erikson’s perspective, uncontrolled online game usage may hinder the successful resolution of the psychosocial crisis of industry versus inferiority, as children tend to derive their sense of achievement and competence more from virtual experiences than from real-life social interactions. However, the study also revealed that when online games are used in a structured, limited manner and under the supervision of teachers and parents, they can serve as a positive learning medium that enhances students’ motivation and engagement.